(3QSGdI NGdO Hf jRjOs - (3eLghds
(3ChdgG (B:s
(3HSe Gddg bGd GYde habc Gddg JYGdi Cf GdTLQI GdJj fgi Gddg YR hLd BOe Ydjg GdUdGI hGdSdGe YfgG gj GdJj hUagG aj cJGHg GdYRjR bGd YR hLd (B{ (3nhnTnLnQkI nJrNoQoL perf oWhpQ nSrjnfGnA nJrfoHoJ pHGdoqOrgpf nhpUrHmZ pdrdBpcpdjnf (B}s
(3BNQgG (B:s
(3gh GdeGA GdNGdO hjSei Hcd SGFd hGdTeS gj GdOgf aef de jYQa JWgjQg Vd hGdeTJQi gh GdUHZ GdCMeQ hGdMeO ddg hMOgs
(3JHUQI GdeDda (B:s
(3efShHI Edi NGdO Hf jRjO Hf eYGhjIs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdcjejGA hGdWHjYjGJs